FAKTOR PENENTU KUALITAS AUDIT (STUDI EMPIRIS PADA KAP DI KOTA SEMARANG) - Andreas Deska Trianto, 13.05.52.0040; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the influence of competence, independence, accountability, time budget pressure, due professional care, task complexity and professional skepticism on audit quality at Public Accounting Firm in Semarang City. The population for this study is all of the auditors who work in Public Accounting Firm in Semarang City. The sampling was done by using convenience sampling method and the number of samples were 71 respondents. The data source is the main data. The method of data collection is done by using questionnaires which delivered directly to the Public Accounting Firm in Semarang City. The method of data analysis used is multiple regression analysis, with the audit quality as dependent variable and competence variable, independence, accountability, time budget pressure due professional care, task complexity and professional skepticism as an independent variable. The results concluded that independence, accountability, time budget pressure, task complexity and professional skepticism have an influence on audit quality. While the competence and due professional care does not influence the quality of the audit.Keywords: Audit Quality, Competence, Independence, Accountability, Time Budget Pressure, Due Professional Care, Task Complexity and Professional Skepticism